Kerjasama Indonesia dengan China Terhadap Impor Buah Jeruk - Karina Saphira (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2019)
This researcher focuses on the relations between countries in the world in the era of globalization in the field of economics, especially trade. Trade activities between countries occur because of the need to meet the market needs of a product, especially citrus fruits from a country because these products cannot be met by domestic production such as Indonesia and China. The fulfillment of the need for these products is done by importing from those countries that produce more of these products. Consumption of citrus fruits in each country is different, for citrus consumption in Indonesia, based on the results of IPB orange Agribusiness Design and Analysis research, estimates of citrus consumption in Indonesia amounted to 1000 tons in 2015. This need cannot be fulfilled due to the production of local citrus in Indonesia amounting to 1611, 784 tons in 2012. Therefore, to meet the needs of oranges in Indonesia, imports were made from China.